2021
DOI: 10.1093/brain/awab208
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for neuropathic pain: a randomized multicentre sham-controlled trial

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has been proposed to treat neuropathic pain but the quality of evidence remains low. We aimed to assess the efficacy and safety of neuronavigated rTMS to the motor cortex (M1) or dorsolateral prefrontal cortex (DLPFC) in neuropathic pain over 25 weeks. We did a randomised double-blind, placebo-controlled trial at four outpatient clinics in France. Patients aged 18–75 years with peripheral neuropathic pain were randomly assigned in a 1:1 ratio t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 49 publications
11
94
0
Order By: Relevance
“…The results for chronic musculoskeletal pain are mirrored in studies on neuropathic pain suggesting that there might be considerable overlap in the brain processes between the two types of pain. This has been demonstrated, for example, very recently in a study by Attal et al (144), where it was shown that M1-rTMS, but not DLPFC-rTMS, induces significant effects on pain intensity changes compared to sham-rTMS.…”
Section: Concluding Remarks and Implications For Clinical Practicementioning
confidence: 75%
“…The results for chronic musculoskeletal pain are mirrored in studies on neuropathic pain suggesting that there might be considerable overlap in the brain processes between the two types of pain. This has been demonstrated, for example, very recently in a study by Attal et al (144), where it was shown that M1-rTMS, but not DLPFC-rTMS, induces significant effects on pain intensity changes compared to sham-rTMS.…”
Section: Concluding Remarks and Implications For Clinical Practicementioning
confidence: 75%
“…A recent large RCT reported that rTMS over the M1 hand area was effective in patients with peripheral neuropathic pain. Approximately 60% of the participants were patients with lower limb pain (Attal et al, 2021). Previous studies have reported the efficacy of rTMS for peripheral neuropathic pain (Lefaucheur et al, 2004;Attal et al, 2016;Pei et al, 2019), and rTMS may be effective for peripheral neuropathic pain regardless of the pain site.…”
Section: Discussionmentioning
confidence: 98%
“…Some other study groups restricted their inclusion criteria to predominantly upper limb pain patients with central post-stroke pain or complex regional pain syndrome, and they also showed that active TMS relieved pain more effectively compared with sham stimulation (Pleger et al, 2004;Picarelli et al, 2010;Ojala et al, 2021). In contrast, some studies have examined the effectiveness of rTMS in alleviating pain at different stimulation sites (Hirayama et al, 2006;Lefaucheur et al, 2006b;Jette et al, 2013;de Oliveira et al, 2014;Lindholm et al, 2015;Ayache et al, 2016;Nurmikko et al, 2016;André-Obadia et al, 2018;Galhardoni et al, 2019;Attal et al, 2021;Freigang et al, 2021;Ojala et al, 2021). We have reported that 5 Hz-rTMS to M1 relieved neuropathic pain, but that to the primary somatosensory cortex, premotor area, and supplementary motor area did not (Hirayama et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the target was controlled using robotic assisted neuronavigation. Results showed that M1 stimulation was effective over 25 weeks with a total of 15 stimulations while DLPFC stimulation was not different from placebo stimulation [24].…”
Section: Neurostimulation Multimodal Approaches and Psychotherapymentioning
confidence: 91%